2020
DOI: 10.1093/tas/txaa003
|View full text |Cite
|
Sign up to set email alerts
|

The effect of varicocele on semen quality in boars exposed to heat stress1

Abstract: Semen quality has a dramatic impact on reproductive efficiency in the swine industry, influencing both conception rate and litter size. The objective of this study was to assess whether the presence of varicocele hinders semen quality in both thermoneutral and heat stress (HS) conditions. At approximately 6 mo of age, ultrasonography was used to measure left and right pampiniform plexus area in order to detect varicocele in maternal line boars at the University of Nebraska–Lincoln. Between 10 and 12 mo of age,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have confirmed the finding. Heat stress decreases the sperm motility or even density, therefore increases sperm deformity and the infertility rate among boars [ 5 ]. In Brangus bulls, similarly, semen quality and the seminal plasma proteome are also changed because of thermal stimulation [ 6 ].…”
Section: The Influence Of Heat Stress On Male Reproductionmentioning
confidence: 99%
“…Previous studies have confirmed the finding. Heat stress decreases the sperm motility or even density, therefore increases sperm deformity and the infertility rate among boars [ 5 ]. In Brangus bulls, similarly, semen quality and the seminal plasma proteome are also changed because of thermal stimulation [ 6 ].…”
Section: The Influence Of Heat Stress On Male Reproductionmentioning
confidence: 99%
“…There has been a direct relationship between varicocele and lower qualities of semen in men referring to infertility clinics ( 3 , 4 ). Scrotal hyperthermia, changes in the bloodstream of the testis, increased venous pressure, hypoxia, hormonal disorders, and accumulation of toxins are the most known factors for the effects of varicocele on the quality of semen ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%